1993
DOI: 10.1262/jrd.39.237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Presence of Glucose during Fertilization and/or Culture in a Chemically Semi-Defined Medium on the Development of Bovine Oocytes Matured and Fertilized in Vitro.

Abstract: Bovine cumulus-oocyte complexes were inseminated in fertilization medium, mBO medium including caffeine (5 mM), heparin (10 ƒÊg/ml) and bovine serum albumin (BSA; 10 mg/ml) with or without glucose (13.9 mM). Oocytes were freed from cumulus cells 8 h post-insemination and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Other reports (Niwa and Ohgoda, 1988;Shioya et al, 1988), showed that in a medium with caffeine or caffeine plus heparin, bovine spermatozoa can be capacitated, and penetrate in the presence of glucose. Finally, irrespective of the presence of glucose, a high penetration rate was obtained in a medium containing caffeine and heparin (Lim et al, 1993;Tajik et al, 1998). Our results confirm that the presence of glucose does not affect penetration by bovine spermatozoa in a medium containing caffeine and heparin or in a medium without bicarbonate.…”
Section: Experiments 5-effect Of Glucose On Sperm Penetrationsupporting
confidence: 79%
See 1 more Smart Citation
“…Other reports (Niwa and Ohgoda, 1988;Shioya et al, 1988), showed that in a medium with caffeine or caffeine plus heparin, bovine spermatozoa can be capacitated, and penetrate in the presence of glucose. Finally, irrespective of the presence of glucose, a high penetration rate was obtained in a medium containing caffeine and heparin (Lim et al, 1993;Tajik et al, 1998). Our results confirm that the presence of glucose does not affect penetration by bovine spermatozoa in a medium containing caffeine and heparin or in a medium without bicarbonate.…”
Section: Experiments 5-effect Of Glucose On Sperm Penetrationsupporting
confidence: 79%
“…Although glucose does not affect fertilization, the presence of glucose during fertilization may be needed for normal development to the blastocyst stage. However, it has been reported that the presence of glucose in the fertilization medium inhibited development to the morula and blastocyst stages (Lim et al, 1993). This discrepancy may arise from the different media for fertilization used in the two studies.…”
Section: Experiments 6-developmental Capacity Of Penetrated Oocytesmentioning
confidence: 94%
“…In particular, glucose at concentrations ranging from 1.5t o 5.56 mM, has been reported to improve blastocyst production both in presence of Ž serum Rorie et al, 1994;Carolan et al, 1995;Koji et al, 1997;Wang et al, 1997; . Ž Donnay et al, 1999 and in the presence of BSA Kim et al, 1993a;Lim et al, 1993Lim et al, , . 1994aOhboshi et al, 1996;Furnus et al, 1997 .…”
Section: Introductionmentioning
confidence: 99%
“…An obvious deficiency in KSOM is the lack of amino acids as precursors for protein synthesis by the blastocyst. Another deficiency at this stage could be the low glucose concentration, as glucose has been found to be especially important at the time of blastocyst formation [8,10,27,28]. However, glucose is not the only source of energy in KSOM.…”
Section: Discussionmentioning
confidence: 99%